Herod and Mariamne A Tragedy in Five Acts by Friedrich Hebbel - Hebbel, Friedrich (UNC Studies in the Germanic Languages and Literatures, 1950)
Originally published in 1950, this volume contains a vivid English verse translation by Paul H. Curts of one of the most profound and moving tragedies of German literature.